2018
DOI: 10.1002/iub.1877
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide analysis of meiotic recombination in yeast: For a few SNPs more

Abstract: Diploid organisms undergo meiosis to produce haploid germ cells. Crossover events during meiosis promote genetic diversity and facilitate accurate chromosome segregation. The baker's yeast Saccharomyces cerevisiae is extensively used as a model for analysis of meiotic recombination. Conventional methods for measuring recombination events in S. cerevisiae have been limited by the number and density of genetic markers. Next generation sequencing (NGS)‐based analysis of hybrid yeast genomes bearing thousands of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Our group had previously isolated and whole-genome sequenced 52 haploid spore clones originated from thirteen sets of JAY270 four-spored tetrads (Rodrigues-Prause et al, 2018). It has been estimated that each meiotic cell division in S. cerevisiae produces about 90 crossovers distributed across the genome (Mancera et al, 2008; Chakraborty et al, 2018). These events result in the formation of recombinant chromatids that are sorted into haploid spores, each containing approximately half maternal and half paternal alleles ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Our group had previously isolated and whole-genome sequenced 52 haploid spore clones originated from thirteen sets of JAY270 four-spored tetrads (Rodrigues-Prause et al, 2018). It has been estimated that each meiotic cell division in S. cerevisiae produces about 90 crossovers distributed across the genome (Mancera et al, 2008; Chakraborty et al, 2018). These events result in the formation of recombinant chromatids that are sorted into haploid spores, each containing approximately half maternal and half paternal alleles ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…This technique is highly scalable, and in our case, we likely could have sequenced many more markers (and/or individuals) while maintaining a very high depth per amplicon. This method is an alternative to the increasingly popular bulk-sequencing approaches, in which sample DNA is pooled prior to sequencing (Chakraborty et al, 2018). GT-seq avoids some of the complexity of these approaches.…”
mentioning
confidence: 99%
“…Similarly, the mean gene conversion tract length in the meiosis of Drosophila melanogaster was determined to be 476 bp ( Miller et al, 2012 ). For gene conversion in the meiosis of Saccharomyces cerevisiae , a somewhat higher value of 1.5 kbp has been obtained ( Chakraborty et al, 2018 ). The very high co-conversion rate in the experiment described above indicated that the value might well be considerable larger in H. volcanii than in all those processes in bacteria and eukaryotes.…”
Section: Discussionmentioning
confidence: 99%